Area-time efficient two-dimensional reconfigurable integer DCT architecture for HEVC - Meher, Pramod Kumar (2021)
In this paper, we present area-time efficient reconfigurable architectures for the implementation of the integer discrete cosine transform (DCT), which supports all the transform lengths to be used in High Efficiency Video Coding (HEVC). We propose three 1D reconfigurable architectures that can be configured for the computation of the DCT of any of the prescribed lengths such as 4, 8, 16, and 32. It is shown that matrix multiplication schemes involving fewer adders can be used to derive parallel architectures for 1D integer DCT of different lengths. A novel transposition buffer is designed to be used for the proposed 2D DCT architecture, which offers double the throughput without increasing the size of the transposition buffer. We determine the optimal pipeline locations in the proposed design through the precise estimation of propagation delays and the critical path so that the area-delay-product is optimized and all the output samples are obtained in the same cycle in spite of the recursive nature of the structure. Implementation results show that the proposed 2D integer DCT architectures provide significantly higher throughput per unit area than the existing designs for HEVC.